2011
DOI: 10.1128/aac.01472-10
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Emergence of Reduced Vancomycin Susceptibility in Health Care-Associated Methicillin-Resistant Staphylococcus aureus Isolates during Continuous-Infusion Vancomycin Therapy in an In Vitro Dynamic Model

Abstract: Bacterial killing and the development of reduced vancomycin susceptibility during continuous-infusion vancomycin (CIV) therapy were dependent on the area under the concentration-time curve over 24 h divided by the MIC (ƒAUC 24 /MIC), with values of >240 (equivalent total serum AUC 24 /MICs of >480) being bactericidal and suppressing emerging resistance in methicillin-resistant Staphylococcus aureus (MRSA). Also, vancomycin therapy was less likely to be bactericidal and 4.4 times more likely to lead to reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Bacterial killing and suppression of vancomycin resistance require an AUC/MIC ratio of 480 when the drug is administered by continuous infusion; this ratio is reached with a steady-state vancomycin concentration of 20 mg/liter when the vancomycin MIC for the pathogen is 1 mg/liter. Given the increasing MICs for clinical isolates of S. aureus, it has been suggested to raise this target concentration to 25 mg/liter (35,36). This suggestion must be taken with caution, since it has been reported that steady-state vancomycin concentrations over 30 mg/liter are related to a higher risk of nephrotoxicity when the drug is administered by continuous infusion (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial killing and suppression of vancomycin resistance require an AUC/MIC ratio of 480 when the drug is administered by continuous infusion; this ratio is reached with a steady-state vancomycin concentration of 20 mg/liter when the vancomycin MIC for the pathogen is 1 mg/liter. Given the increasing MICs for clinical isolates of S. aureus, it has been suggested to raise this target concentration to 25 mg/liter (35,36). This suggestion must be taken with caution, since it has been reported that steady-state vancomycin concentrations over 30 mg/liter are related to a higher risk of nephrotoxicity when the drug is administered by continuous infusion (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic expression of low-level glycopeptide resistance is variable, being significantly influenced by several technical parameters, including the compositions of liquid or solid test media and various time frames and inoculum sizes (24,28,49,51). Since broth microdilution and agar dilution assays use inadequate inocula and too-short incubation periods for reliable detection of some hGISA isolates (25,42,47,51), alternative GISA detection methods, such as the PAP-AUC, Etest macromethod, and Etest GRD, have been proposed (summarized in references 24 and 49) and repeatedly tested in vitro (26,41,45,50,55). Despite their merits, these alternative GISA detection methods have generated complex results that can hardly be integrated into the current schemes of glycopeptide MIC breakpoints.…”
Section: Discussionmentioning
confidence: 99%
“…A PD study reasserted that bacterial killing and development of diminished vancomycin susceptibility during CoI therapy were dependent on the AUC/MIC ratio, with values of 480 being bactericidal and suppressing emerging resistance; this target would be achieved with CoI at a steady-state concentration of 20 mg/liter when vancomycin pathogen MICs are 1 mg/liter (40). Other authors have suggested that, given the tendency toward increasing vancomycin MICs in clinical isolates of S. aureus in some centers, a target concentration of 25 mg/liter may be more appropriate (41).…”
Section: Intermittent Versus Continuous Infusion Therapymentioning
confidence: 99%